ORIGIN OF MORB AND CHEMICALLY-DEPLETED MANTLE RESERVOIRS: TRACE ELEMENT CONSTRAINTS - Saunders A.D.; Norry M.J.; Tarney J. (My University, 1988)
The depleted chemical signature of MORB has been commonly thought to be a consequence of the progressive extraction of continental crust from the upper mantle, although few attempts have been made to evaluate the exact nature of the depletion process. The spectrum of MORB compositions, at least in terms of Ba, Th, K, Pb, U, Ce and Nb data, cannot be accommodated by extraction of continental crust alone. Development of the MORB reservoir (Depleted MORB Mantle or DMM) began early in Earth history by extraction of incompatible elements from the upper mantle into the oceanic crust. This resulted in a chemically-zoned upper mantle, with strong depletion of the highly-incompatible elements. However, the necessary fractionation of Nb from K and other incompatible elements was achieved by removal at subduction zones of a large-ion lithophile element (LILE: K, Ba, Rb, etc.) rich and Nb-depleted fluid (here termed the Slab Derived Component (SDC)), from the Residual Slab Component (RSC). The eclogitic LILE-depleted RSC was variably remixed in the lower mantle, possibly with primordial mantle and minor volumes of SDC (as continental crust or lithosphere) to produce a niobium-rich reservoir, the complement to the Nb-deficient continental crust. Remixing of this material with DMM in the upper mantle is better able to account for the spectrum of MORB compositions. The presently available trace element and isotope data preclude significant recycling of continental crust into the MORB mantle, although a component of such material appears to be necessary to produce the spectrum of ocean island basalt compositions.